Improving Ballastless Track Quality Using Project Quality Management and SmartPLS - Putri Elsari Rahmayana; Humiras Hardi Purba; Budi Susetyo (Bina Nusantara University, 2021)
Transportation is still a significant problem in Indonesia. Indonesians prefer to use private vehicles for daily mobility purposes because public transportation lacks safety and comfort and has a longer trip duration. This issue causes congestion and air pollution problems. Hence, sustainable railbased public transportation is recommended. Light Rail Transit (LRT) tends to be congestion-free and has a relatively shorter travel time with a large passenger capacity. Most LRT track constructions use the ballastless track. However, this track construction is still new in Indonesia. The research aimed to determine the most important factors in improving ballastless track construction performance on LRT. The research referred to the existing LRT construction in Indonesia using Lean Construction (LC) and Project Quality Management (PQM) approaches. Statistical science approach with SmartPLS software was also used in data processing and modeling the relationship between variables. The research was conducted by distributing questionnaires to determine the most important factors in improving the quality of ballastless tracks with variables and indicators extracted from LC and PQM methods. From five tested hypotheses, only one hypothesis is accepted. Quality control has a positive effect on track quality. It is also found that quality control becomes the most important variable in improving ballastless track quality.